PENINGKATAN PERAN AKTIF PEREMPUAN PEDESAAN MELALUI MODEL KELOMPOK BELAJAR TERPADU DALAM UPAYA MELESTARIKAN FUNGSI SUNGAI GEDANGAN DAN SUNGAI PEPE SIDOARJO Asri Wijiastuti dan Siti Masitoh (Lentera, Jurnal Studi Perempuan, 2010)
Abstraet The result ofCollaborations Learning Group Model (MKBT) development â *zs consist of: (1) MKBT Guidcinc e, and (2) Booklet Media series 1 and 2 w e re * i forts attUude and behaviour changed loward awareness in conservation of wtkt fiinetion district women who lived in along the Gedangan and the Pepe tnvrbank side Sidoarjo. IJntil nowdays community in along riverbank tend med river or riverbank for disposal waste, because they w e re have opinion if ’wht river w as for to disposal waste. This condition needs solutions alfernative wtiir. 10 change community attitude and behaviour through active involvement 4b conservation of river fimetion w i (h waste management. MKBT development p auempt to increased active involvement (awareness) district women in wmtser’ation of river funetion. trpvords : district women/perempuan pedesaan, conservation of river